The Emergence and Performance of New Technology-Based Firms in Nigeria - Adeyinka, Foluso Modupe; Wahab, Bashir Adelowo (Journal of Technology Management and Business, 2022)
New Technology-Based Firms (NTBFs) are one of the key actors within the National System of Innovation. They are firms/businesses based on the exploitation of an invention and they play crucial roles in the processes of bringing new ideas or innovations to the market and by extension, contributing to economic growth. This paper provides empirical evidence on the emergence and performance of NTBFs in Nigeria. A survey design was used to collect data from NTBFs in the selected Technology Incubator Centres (TICs). Data were analysed using both descriptive statistics and the ordinary least square technique. The research results show that research and development (R&D) activities are vital for the growth and development of NTBFs, but this activity is still at a very minimal level. Product price, the number of employees, research and development, access to credit facilities, and the cost of raw materials are statistically significant in explaining the performance of NTBFs. The recommendations for ensuring the improved performance of NTBFs in Nigeria include the increased collaboration among NTBFs, universities, and research institutes, firms to spend at least 40 percent of their profit on research and development that relates to the improvement of their products, and the improvement in the level of the production process to enhance productivity and competitiveness.